Perceção dos pais relativamente aos comportamentos alimentares das suas crianças: comparação entre crianças prematuras e crianças de termo. - Inês Vasconcelos Bouça Pinheiro (2023)
Feeding is a complex process, and that's why feeding difficulties are so common in early childhood. Prematurity appears to be a risk factor for increased feeding problems, so our goal was to evaluate the effect of prematurity on children's feeding behavior. We also intended to identify situations that have a significant impact on the child's and family's life and refer them to a specialized consultation. In our study participated 109 children (51 preterm and 58 full-term), whose parents answered the Behavioral Pediatrics Feeding Assessment Scale and a demographic questionnaire. It was found that the perception of feeding difficulties is higher in parents of preterm children, likewise the perception of those problems, and although not statistically significant, the risk of feeding difficulties is higher in the preterm group compared to the other one.